Answer:
This statement can be written using predicate logic thus;
(there exists x)(for all y)[M(x) ∧ R(x,y)] ∧ (for all x)(for all y)[R(x,y) → T(x,y)] → (there exists x)(for all y)[M(x) ∧ T(x,y)]
Proof:
- (there exists x)(for all y)[M(x) /\ R(x,y)] HYP
- (for all x)(for all y)[R(x,y)-> T(x,y)] HYP
- (for all y)[M(s) /\ R(s,y)] EI,1
- M(s) /\ R(s,y) UI,3
- (for all y)[R(s,y)-> T(s,y)] UI,2
- R(s,y)-> T(s,y) UI,5
- R(s,y) Simp,4
- T(s,y) MP,6,7
- M(s) Simp,4
- M(s) /\ T(s,y) Conj,7,9
- (for all y)[M(s) /\ T(s,y)] UG,10
- (there exists x)(for all y)[M(x) /\ T(x,y)] EG,11